2006
DOI: 10.1021/jo061017o
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Tetrahydrofuran Synthesis via 1,4-Butanediol Dehydration in High-Temperature Water

Abstract: We conducted an experimental investigation into the kinetics and mechanism of tetrahydrofuran synthesis from 1,4-butanediol via dehydration in high-temperature liquid water (HTW) without added catalyst at 200-350 degrees C. The reaction was reversible, with tetrahydrofuran being produced at an equilibrium yield of 84% (at 200 degrees C) to 94% (at 350 degrees C). The addition of CO2 to the reaction mixture increased the reaction rate by a factor of 1.9-2.9, because of the increase in acidity resulting from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 36 publications
5
92
0
Order By: Relevance
“…It has been reported that it transforms into tetrahydrofuron when the temperature and pressure exceed 250°C and 18 MPa [24]. In the present case, where the temperature exceeded the critical value but the pressure did not, the functional groups from the precursors were suspected to have reacted with the butanediol derivatives, possibly leading to a different reaction pathway (see GC-MS data) compared with the normal tetrahydrofuron transformation.…”
Section: Formation Mechanismmentioning
confidence: 54%
“…It has been reported that it transforms into tetrahydrofuron when the temperature and pressure exceed 250°C and 18 MPa [24]. In the present case, where the temperature exceeded the critical value but the pressure did not, the functional groups from the precursors were suspected to have reacted with the butanediol derivatives, possibly leading to a different reaction pathway (see GC-MS data) compared with the normal tetrahydrofuron transformation.…”
Section: Formation Mechanismmentioning
confidence: 54%
“…The decrease of the pH from 5 to 3 during our tests indicates that high concentrations of protons are generated by self-ionization of water molecules under the chosen hydrothermal conditions [43]. That means the dehydration of sorbitol to isosorbide could be affected by the proton concentration.…”
Section: Effect Of Aciditymentioning
confidence: 76%
“…c The sample is the same as that listed in Table 3 acidified conditions accelerate the reaction rate. 104 Richter and Vogel have reported that the THF selectivity is nearly 100% by the use of pure supercritical water as the reaction media. 106 Besides, several papers described that THF as the primary product from 1,4-BDO could be dehydrated into BD, even though the process needs strict conditions.…”
Section: Dehydration Of 14-bdomentioning
confidence: 99%